Economic Financial Viability of an agroecological model in a quilombolas community (Research, Society and Development, 2019)
Traditional communities are in a large number distributed in Brazilian territory. The quilombolas are traditional groups from old quilombos. In São Mateus is located the community from Divino Espírito Santo. Traditional communities use agricultural activities as income generating activities, however, they do not use techniques to know the viability. The research analyses the viability of the proposed property in Divino Espírito Santo community, using finance data, as billing, expenses and costs, as basis. The objective is calculated the finance indicator and analyze the viability of the Project. From the feasibility analysis, the present study proposes to verify in which aspects the property becomes unfeasible and presents possible solutions with the reality found. The indictors mark the Project as unviable, in one of the three scenarios. The socio-economic profile of the community and SWOT show that is possible to turn the scenario in positive.